2015
DOI: 10.1007/s13311-015-0380-8
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Toxicology of Cannabinoids

Abstract: There is extensive research on the safety, toxicology, potency, and therapeutic potential of cannabis. However, uncertainty remains facilitating continued debate on medical and recreational cannabis policies at the state and federal levels. This review will include a brief description of cannabinoids and the endocannabinoid system; a summary of the acute and long-term effects of cannabis; and a discussion of the therapeutic potential of cannabis. The conclusions about safety and efficacy will then be compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 119 publications
2
57
0
4
Order By: Relevance
“…Despite the therapeutic potential of cannabinoids, the current findings present evidence on acute adverse effects of cannabinoid‐based drug use . The magnitude of these adverse effects is dependent on several factors, including early age of first use and the cannabinoid concentration within the product .…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Despite the therapeutic potential of cannabinoids, the current findings present evidence on acute adverse effects of cannabinoid‐based drug use . The magnitude of these adverse effects is dependent on several factors, including early age of first use and the cannabinoid concentration within the product .…”
Section: Discussionmentioning
confidence: 88%
“…Parallel to the rise in the popularity of cannabis use, numerous studies have indicated the therapeutic potential of cannabis and its derivatives for a range of health conditions, including neurological and psychiatric disorders ( Table ). However, despite the suggested therapeutic potential of cannabinoid‐based medications current studies have indicated inconclusive results regarding the efficacy of medical cannabis in certain conditions . Furthermore, additional publications have shown that repeated exposure to cannabinoid agonists is associated with increasing risk for having somatic and psychological side effects, including respiratory and cardiovascular disorders, cognitive alterations, addiction, psychosis, schizophrenia, and mood disorders .…”
Section: Common Clinical Adverse Effects Associated With Cannabinoidsmentioning
confidence: 99%
See 2 more Smart Citations
“…19 • Cannabis e condução: O consumo de cannabis parece aumentar duas a sete vezes o risco de acidentes de viação. 20,21 • Risco da dependência: Sugere-se que cerca de um em cada 11 utilizadores se torna consumidor sistemático de cannabis. 22,23 Este número aumenta entre aqueles que começam na adolescência (até cerca de 17%, ou um em cada 6) 24 e entre pessoas que usam cannabis diariamente (até 25% -50%).…”
unclassified